Durability of etics incorporating high reflectance pigments in finishing coatings - Nuno M. M. Ramos (2020)
The increase of the durability of building materials and components presents great importance since it contributes to a more sustainable environment by increasing its service life. The development of new building materials and technologies with improved thermal characteristics, such as ETICS with high reflectance coatings, contributes to meet the thermal requirements defined by the European regulation. However, the importance of the durability assessment of new solutions cannot be understated as it plays a key role in the prevention of future early degradation. This paper has the objective of assessing the durability of ETICS incorporating high reflectance pigments in organic coatings. The solar reflectance can be increased through optimized material formulations with the inclusion of nanoparticles in coatings. If the near-infrared (NIR) solar absorption is reduced, the referred benefits can be achieved even in darker colours. One of the main concerns is the durability of the entire system, but the stability of the darker colours must also be taken into account. As such, relevant parameters solar absorptance, surface temperature and colour were measured in a long-term in-situ experimental campaign, in ETICS specimens with distinct coatings. The effect of the thermal insulation layer, in the referred parameters, was also evaluated, by measuring the effect of the same coatings in samples with traditional substrates. The solar absorptance was measured with a pyranometer with an adapted methodology based on the ASTM E1918 standard. The surface temperature of the samples was continuously monitored for an extended period enabling a comparison of the benefits under different climatic conditions. The colour was determined by the CIELAB colour space, by measuring the L*A*B parameters. The results showed that the incorporation of high reflectance pigments leads to a decrease in the solar absorptance and surface temperature even in darker colours. The pigments also influenced the lightness of the coating, by increasing the L parameter. The potential benefits of these thermal enhanced systems combine an enhanced thermal performance, durability and a higher diversity of aesthetic features.